2014
DOI: 10.1016/j.jceh.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Nodule in Liver: Investigations, Differential Diagnosis and Follow-up

Abstract: Conventional ultrasonogram of the abdomen being noninvasive, inexpensive and ubiquitously available is the first imaging modality that raises suspicion of HCC in a patient with chronic liver disease with or without cirrhosis. The lesions in liver particularly nodule are being recognized with increased frequency with the wide spread use of ultrasonogram as the initial investigation and computerized tomography and magnetic resonance imaging subsequently. Any nodule in a cirrhotic liver should be considered as he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
1
15
1
1
Order By: Relevance
“…In the hands of an experienced examiner, CEUS is a useful diagnostic method to evaluate the dynamic micro-vascularization of malignant liver tumors [16,20] and to detect remaining tumor vascularization after interventional treatment [21,22]. Furthermore, it has proven to be as accurate as other contrast-enhanced imaging (ceCT/ceMRI) modalities for the assessment of technical success after RFA [23 -25].…”
Section: Discussionmentioning
confidence: 99%
“…In the hands of an experienced examiner, CEUS is a useful diagnostic method to evaluate the dynamic micro-vascularization of malignant liver tumors [16,20] and to detect remaining tumor vascularization after interventional treatment [21,22]. Furthermore, it has proven to be as accurate as other contrast-enhanced imaging (ceCT/ceMRI) modalities for the assessment of technical success after RFA [23 -25].…”
Section: Discussionmentioning
confidence: 99%
“…Capsule, heterogeneity, and mosaic pattern could be observed in HCC by MRI [124]. The combination of hypervascularity in the arterial phase with washout in the portal venous or delayed phase, which are 'classical imaging features,' is highly specific for the diagnosis of HCC [127]. However, the specificity is not 100%.…”
Section: Abdominal Ct and Mrimentioning
confidence: 99%
“…2 It has been reported previously that 41-62% of lesions <2 cm in diameter show either an absence of arterial hypervascularity or venous washout. 3 In addition, the malignant transformation rates at 5 years were estimated to be 30-80% for highand low-grade dysplastic nodules and 12% for regenerative nodules. 15,20,21 We also have examined the clinical course of 18 adenomatous hyperplasias of the liver and found that 9 developed into HCC during the 1-to 5-year follow-up periods.…”
Section: Discussionmentioning
confidence: 99%